Preparation and Mechanical Properties of Graphene Oxide: Cement Nanocomposites - Fakhim Babak; Hassani Abolfazl; Rashidi Alimorad; Ghodousi Parviz (The Scientific World Journal)
We investigate the performance of graphene oxide (GO) in improving mechanical properties of cement composites. A polycarboxylate superplasticizer was used to improve the dispersion of GO flakes in the cement. The mechanical strength of graphene-cement nanocomposites containing 0.1–2 wt% GO and 0.5 wt% superplasticizer was measured and compared with that of cement prepared without GO. We found that the tensile strength of the cement mortar increased with GO content, reaching 1.5%, a 48% increase in tensile strength. Ultra high-resolution field emission scanning electron microscopy (FE-SEM) used to observe the fracture surface of samples containing 1.5 wt% GO indicated that the nano-GO flakes were well dispersed in the matrix, and no aggregates were observed. FE-SEM observation also revealed good bonding between the GO surfaces and the surrounding cement matrix. In addition, XRD diffraction data showed growth of the calcium silicate hydrates (C-S-H) gels in GO cement mortar compared with the normal cement mortar.